Fences - Washington, Denzel 1954-; Davis, Viola 1965-; Wilson, August (Paramount, 2017)
A black garbage collector named Troy Maxson in 1950s Pittsburgh is bitter that baseball's color barrier was only broken after his own heyday in the Negro Leagues, Maxson is prone to taking out his frustrations on his loved ones
Title from web page
Based on August Wilson's Pulitzer prize-winning novel
Originally released as a motion picture in 2016
Widescreen
Keywords: USA; Families, Black / United States / Drama; Families / Drama; Fathers and sons / Drama; Fathers and sons / United States / Drama; Man-woman relationships / Drama; Negro leagues / Drama; Race relations / Drama; African American theater / New York (State) / New York; Theater / New York (State) / New York; Feature films